1990
DOI: 10.1007/bf00294214
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA encoding the scrapie agent protein is present in a variety of non-neuronal cells

Abstract: PrP 27-30, a unique protease-resistant protein associated with scrapie infectivity, derives from the proteolytic cleavage of a larger precursor encoded by a host gene. To identify sites of PrP biosynthesis, in situ hybridization was done using cloned PrP cDNA as a probe. In rodent brain, PrP mRNA was expressed in neurons, ependymal cells, choroid plexus epithelium, astrocytes, pericytes, endothelial cells and meninges of both scrapie-infected and uninfected animals. PrP mRNA was also detected in vitro in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…Gavrilina et al (2008) reported that a small increase of SMN in neurons strikingly extended the survival of severe SMA mice carrying an SMN cDNA transgene driven by a neuronspecific promoter. However, the mouse prion promoter used in that study is also active in many nonneuronal cell types and peripheral tissues (Brown et al 1990), which may have contributed to phenotypic rescue. Indeed, several recent studies using various mouse models showed that restoring SMN expression only in motor neurons or pan-neuronally resulted in a limited survival increase (Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Gavrilina et al (2008) reported that a small increase of SMN in neurons strikingly extended the survival of severe SMA mice carrying an SMN cDNA transgene driven by a neuronspecific promoter. However, the mouse prion promoter used in that study is also active in many nonneuronal cell types and peripheral tissues (Brown et al 1990), which may have contributed to phenotypic rescue. Indeed, several recent studies using various mouse models showed that restoring SMN expression only in motor neurons or pan-neuronally resulted in a limited survival increase (Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Total RNA was extracted and purified with the RNA NOW kit (Biogenetex, Seabrook, TX) as recommended by the supplier. For cDNA synthesis, 2 g of total RNA was heat-denatured for 3 min at 70°C and reverse-transcribed with 200 units of Superscript II RNaseH Ϫ Reverse Transcriptase (Life Technologies, Paisley, Scotland) in 20 l of 1ϫ incubation buffer (provided by the supplier) supplemented with 10 mM DTT, 1 mM dNTP, 1 unit͞ l RNAsin (Promega), and 0.5 g of (dT) [12][13][14][15][16][17][18] primers (Amersham Pharmacia). Two microliters of each cDNA reaction was subjected to PCR amplification with 25 pmol each of the sense and antisense primers in 50 l 1ϫ PCR buffer, 0.2 mM dNTP, and 1 unit recombinant Taq DNA polymerase (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…The PrP c gene has been described as a housekeeping gene with a preferential expression in neurons (13)(14)(15). PrP c has been shown to be present in various regions of the hamster brain, including cortex, hippocampus, striatum, olfactory bulb, hypothalamus, midbrain, cerebellum, and brainstem (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations